Fuzzy Mean e-Open and e-Closed Sets (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The notions of fuzzy mean e -open and e -closed sets is established. Moreover, some comparative study of these with other fuzzy mappings are investigated. Finally, we extend fuzzy mean e -open to fuzzy para e -open sets in fuzzy topology.